Strategi Pengelolaan dan Pengembangan Pariwisata Dalam Meningkatkan Pendapatan Masyarakat Mandailing Natal Perspektif Ekonomi Islam Dengan Pendekatan QSPM - Nurul Hasanah Nasution; Maryam Batubara; Muhammad Arif (ITB AAS INDONESIA Surakarta, 2022)
Mandailng Natal regency is one of the parisiwata sectors that have the potential to be managed, developed and socialized to the wider community. There are 150 tourist destinations in almost every district. The results of the review found that about 65 percent of tourist attractions in Mandailing Natal Regency have not been managed properly. Attractions that have the potential to attract more visitors if developed with a good strategy. The purpose of the study is to analyze tourism management and development strategies in increasing community income in Mandailing Natal Regency. This study uses descriptive qualitative methods, data collected by conducting interviews and dissemination of quantoners and then the data that has been collected is analyzed using QSPM analysis. The results of the study are, the right strategy applied based on QSPM analysis related to four analyses is to increase the conscious socialization of tourism to the community, improve the quality of tourism